Paciente femenino de 50 años de edad con problemas de insuficiencia de convergencia. - Galarza Robi, Doménica Lorena (2020)
The present clinical case refers to a 50-year-old patient who has been diagnosed with convergence insufficiency (IC). IC is the most common binocular vision alteration, it is characterized by muscle coordination problems, where the eyes cannot work together when fixing their eyes on a certain point, because the eye deviates outward causing blurred vision when performing tasks closely. The objective of the research is to determine the effects of convergence insufficiency in a 50-year-old patient. The applied methodology is based on the analysis of the clinical history, pathological antecedents, physical examinations (radiography, fundus, biomicroscopy,, AVL, AVC, AVCC, ocular motility) and complementary, which served to make a definitive diagnosis and prescribe treatment according to condition. The results obtained during the research process were: the risk factors associated with the disease are due to age and the lack of visual examinations; the symptoms that the patient presents are: eye fatigue, eye pain, asthenopia, frontal headache, blurred vision and double vision; The established treatment to mitigate the ocular problem is based on the therapy of push-up and optical correction. The conclusion of the study is that a significant reduction in his problem was archieved , so the use of reading glasses was recommend to maintain binocular vision when perfoming close-up tasks.